2002
DOI: 10.1038/415918a
|View full text |Cite
|
Sign up to set email alerts
|

Numerical representation for action in the parietal cortex of the monkey

Abstract: The anterior part of the parietal association area in the cerebral cortex of primates has been implicated in the integration of somatosensory signals, which generate neural images of body parts and apposed objects and provide signals for sensorial guidance of movements. Here we show that this area is active in primates performing numerically based behavioural tasks. We required monkeys to select and perform movement A five times, switch to movement B for five repetitions, and return to movement A, in a cyclica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
173
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(187 citation statements)
references
References 21 publications
11
173
1
2
Order By: Relevance
“…In particular, a small area of the left and right intraparietal sulci is systematically activated whenever numerical quantities are manipulated (Dehaene, Piazza, Pinel, & Cohen, 2003). Recently, a possible homolog of this area has been identified in the intraparietal sulcus of macaque monkeys, further strengthen-ing the hypothesis that number sense in humans has a long evolutionary history (Sawamura, Shima, & Tanji, 2002).…”
Section: Introductionsupporting
confidence: 48%
“…In particular, a small area of the left and right intraparietal sulci is systematically activated whenever numerical quantities are manipulated (Dehaene, Piazza, Pinel, & Cohen, 2003). Recently, a possible homolog of this area has been identified in the intraparietal sulcus of macaque monkeys, further strengthen-ing the hypothesis that number sense in humans has a long evolutionary history (Sawamura, Shima, & Tanji, 2002).…”
Section: Introductionsupporting
confidence: 48%
“…This kind of normalisation process is typical of the computations attributed to parietal cortex, a high order cortex that receives direct and indirect projections from all sensory regions, activated in many tasks that involve attention and coordinates transformation in both spatial and temporal domains (Culham and Kanwisher, 2001;Duhamel et al, 1992). Numerosity sensitive cell assemblies in monkeys and cats have been found by electrophysiological recordings from areas that are homologous to parietal regions (Nieder and Miller, 2004;Sawamura et al, 2002;Thompson et al, 1970). According to the present proposal, then, the process of abstraction of numerosity could primarily be a function of the parietal cortex.…”
Section: An A-modal Right Hemisphere Superiority For Approximate Numementioning
confidence: 90%
“…While these models are successful in predicting behaviour, they do not provide information with respect to the implementation of these mechanisms in the human (or animal) brain. However, recent electrophysiological studies have considerably improved our understanding of the neural bases of number sense, demonstrating the existence of cells that show preferential responses to a given numerosity (number coding cells) located both in the fundus of the intraparietal sulcus and in the lateral pre-frontal cortex between inferior arcuate sulcus and the principal sulcus (Nieder et al, 2002;Sawamura et al, 2002;Thompson et al, 1970). In particular, Nieder and Miller (2004) showed that neurons in the intraparietal sulcus responded to and conveyed numerosity information earlier than prefrontal neurons, suggesting that numerosity information is primarily extracted in the posterior cortex and only successively transmitted to the frontal cortex.…”
Section: Estimationmentioning
confidence: 99%
“…Neurons in the primate parietal cortex display number-selective activity while performing numerically based behavioral tasks (Sawamura et al, 2002). This numberselective activity is classified as early-, late-, or middle-trial selective, according to its temporal preference.…”
Section: All-or-none Type Intermediate Typementioning
confidence: 99%
“…6 E, F ). Such numerical representation may be useful for monitoring execution of individual actions and keeping track of the number of actions performed, to select an appropriate forthcoming action (Sawamura et al, 2002).…”
Section: All-or-none Type Intermediate Typementioning
confidence: 99%